Undergraduate experience of ENT teaching during the coronavirus disease 2019 pandemic: a qualitative study. Issue 8 (28th August 2021) - Walker, M; Stapleton, E
Abstract: Background: Coronavirus disease 2019 has transformed medical education worldwide. Innovations in ENT teaching for medical students have focused on virtual learning, often replacing history-taking, patient examination and practical procedure observation. This qualitative study aimed to evaluate student experience and the impact of the altered learning environment. Methods: Open-ended questionnaires were sent to students following ENT placements from March 2020 to March 2021. Responses were qualitatively analysed and coded using a grounded theory approach. Iterative cycles were used to develop codes via a constant comparison technique. Emerging categories from codes were refined to identify core themes. Results: Core themes were explored, including: reduced clinical experience and patient contact compared with student expectations; challenges to learning opportunities in ENT; and the experience of different teaching methods, or preference for face-to-face teaching. Conclusion: Medical students on ENT placement have expectations of patient contact for learning opportunities. ENT departments should ensure that patient contact and face-to-face learning opportunities are facilitated, while maintaining safety, including appropriate personal protective equipment provision.